2010
DOI: 10.1016/j.ejcts.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The modified Ross operation using a Dacron prosthetic vascular jacket does prevent pulmonary autograft dilatation at 4.5-year follow-up

Abstract: Provision of external support to the entire pulmonary autograft with a DVPJ prevents its dilatation following free-standing pulmonary autograft Ross operation when evaluated at the 4.5-year follow-up. The function and the geometry of the neo-aortic root are not affected negatively by this modification and the patients demonstrated normal exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…[ 57 ] In the more recent years the application of a Dacron tube for external support of the pulmonary autograft, to prevent sinus and sinotubular junction dilatation in freestanding roots, has gained renewed interest. [ 67 ] A combined ascending aortic replacement for aneurysm had no influence on late autograft function in a 5-year follow-up study, but the long-term fate of the neo-aortic valve in this setting is not known. [ 59 ]…”
Section: Primary Aortic Dilatation Associated With Chdmentioning
confidence: 99%
“…[ 57 ] In the more recent years the application of a Dacron tube for external support of the pulmonary autograft, to prevent sinus and sinotubular junction dilatation in freestanding roots, has gained renewed interest. [ 67 ] A combined ascending aortic replacement for aneurysm had no influence on late autograft function in a 5-year follow-up study, but the long-term fate of the neo-aortic valve in this setting is not known. [ 59 ]…”
Section: Primary Aortic Dilatation Associated With Chdmentioning
confidence: 99%
“…27-29 The Ross procedure increasingly is being performed with reinforcement of the aortic root to prevent dilation and associated aortic insufficiency. 30,31 The Norwood operation differs from the Ross and arterial switch operations because the entire ascending aorta is reconstructed, and, as we demonstrate, dilation extends beyond the aortic root into the ascending and transverse arch.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike pericardium, Dacron polyester fabric has no potential to contract or calcify with time. Al Rashidi and colleagues 3 have shown that reinforcement of the autograft prevents dilation as long as 4.5 years with a tube graft. We believe that the native shape of the neoaortic sinuses is preserved by the use of the Valsalva graft.…”
Section: Discussionmentioning
confidence: 99%